Removal of Di (2-ethylhexyl) phthalate from groundwater by sodium persulfate activated by hollow micron zero-valent iron: Reaction mechanism and degradation path - Chunyang Gao; Bing Wang; Jingjing Zhao; Jvfeng Li; Xianyuan Du; Jin Zheng; Quanwei Song; Jiacai Xie (Ecotoxicology and Environmental Safety)
In this study, hollow micron zero-valent iron (H-mZVI) was prepared using the ethylenediamine liquid phase reduction method. The microstructures were characterized by SEM, XRD, BET and FTIR. The results showed that H-mZVI possessed a spherical hollow structure with a particle size of approximately 1 μm. The density of H-mZVI was notably lower compared to solid micron zero-valent iron (S-mZVI). Furthermore, with an increase in ethylenediamine addition, the density initially decreased before stabilizing. Results demonstrated that the degradation efficiency of H-mZVI/PS for DEHP was 2.96 times higher than that of S-mZVI/PS. The charge density of H-mZVI/PS degradation DEHP system was higher than that of S-mZVI/PS system, and H-mZVI exhibited a fast electron migration rate and strong electron transport ability between the solution and the interface material. The degradation of DEHP by H-mZVI/PS system was carried out jointly by the surface reaction on the surface of H-mZVI particles and the homolytic reaction led by Fe2+ ions in the solution. Additionally, the contribution rate of free radicals in the degradation process of DEHP was in the order SO4-· > ·OH > 1O2. There were three degradation pathways of DEHP in H-mZVI/PS system, and the toxicity of DEHP degradation products was significantly lower than that of the parent.